MSVPWM Based-SAPF For Harmonic Mitigation in The Distribution Network Under Unbalanced Condition - Husen, Haider Muhamad; Ahmed Qadir, Salar (Kurdistan Journal of Applied Research, 2020)
Unbalanced input source voltages generate extra current harmonics in addition to non-linear loads which distorts the power quality in the entire power systems. Three-phase multi-level neutral point clamped (NPC) converter based shunt active harmonic filter (SAHF) are used as a solution to overcome problems due to current harmonics. In this work, synchronous reference frame (d-q) algorithm is selected to detect the harmonic current components, Proportional-integral (PI) controller is utilized to ameliorate the storage of energy in the dc-link capacitor and the multilevel space vector pulse width modulation (MSVPWM) strategy determines the switching pulses of NPC inverter. Under balanced input supply voltages condition, the proposed MSVPWM achieved a mitigation of source current THD of 3.58 % as compared to 28.57 % prior to compensation on non-linear load. Furthermore, the MSVPWM technique was compared with and without compensation under unbalanced input source voltages and the results shows that the proposed method achieved reduction in source current THD of 3.96 % as compared to 29.76 % after and before compensation respectively. The proposed MSVPWM based-SAPF model was also compared with conventional SVPWM under balanced and unbalanced input supply voltages conditions. The results show that MSVPWM performed better than CSVPWM. The simulated results obtained by MATLAB/SIMULINK power system environment. All the results for the presented work are within IEEE-519 harmonics standard with non-linear loads under balanced and unbalanced voltages condition.